Understanding interpersonal relationships and psychopathy. Issue 4 (4th July 2019) - Mooney, Robyn; Ireland, Jane L.; Lewis, Michael
ABSTRACT: Although psychopathy is widely recognised for its importance in forensic and criminal justice settings, the range of interpersonal relationships that are experienced and engaged in by individuals with psychopathy is understudied. A Rapid Evidence Assessment (Study 1) examined what is known empirically about the nature and quality of relationships for individuals with psychopathy. Affective, Cognitive and Lifestyle Assessment (ACL) interviews comprising genograms were then analysed in conjunction with Psychopathy Checklist: Screening Version (PCL:SV) scores to explore the extent, nature, and quality of interpersonal relationships in student and forensic psychiatric samples (Study 2). Quantitative data indicated that total psychopathy score predicted a smaller number of positive interpersonal relationships. Findings regarding Factors 1 and 2 and numbers of positive and negative interpersonal relationships varied between samples. Qualitative analyses demonstrated that psychopathic participants used less positive descriptors than non-psychopathic participants when discussing their interpersonal relationships. Findings are examined with regards to implications for future research.